Level ground and uphill cycling efficiency in seated and standing positions - Millet, G. P.; Tronche, C.; Fuster, N.; Candau, R. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: This study was designed to examine the effects of cycling position (seated or standing) during level-ground and uphill cycling on gross external efficiency (GE) and economy (EC). METHODS: Eight well-trained cyclists performed in a randomized order five trials of 6-min duration at 75% of peak power output either on a velodrome or during the ascent of a hill in seated or standing position. GE and EC were calculated by using the mechanical power output that was measured by crankset (SRM) and energy consumption by a portable gas analyzer (Cosmed K4b(2)). In addition, each subject performed three 30-s maximal sprints on a laboratory-based cycle ergometer or in the field either in seated or standing position. RESULTS: GE and EC were, respectively, 22.4 +/- 1.5% (CV = 5.6%) and 4.69 +/- 0.33 kJ x L(-1) (CV = 5.7%) and were not different between level seated, uphill seated, or uphill standing conditions. Heart rate was significantly ( < 0.05) higher in standing position. In the uphill cycling trials, minute ventilation was higher ( < 0.05) in standing than in seated position. The average 30-s power output was higher ( < 0.01) in standing (803 +/- 103 W) than in seated position (635 +/- 123 W) or on the stationary ergometer (603 +/- 81 W). CONCLUSION: Gradient or body position appears to have a negligible effect on external efficiency in field-based high-intensity cycling exercise. Greater short-term power can be produced in standing position, presumably due to a greater force developed per revolution. However, the technical features of the standing position may be one of the most determining factors affecting the metabolic responses.